LOGIKA FUZZY MAMDANI DAN ALGORITMA DIJKSTRA UNTUK MANAJEMEN KESELAMATAN PADA PENCARIAN RUTE - Mochammad Firman Arif; Muhammad Misdram (SPIRIT, 2019)
Congestion in Malang has become a common sight. The government has done a lot of ways to overcome these bottlenecks, such as the construction of flyovers and underpasses, the operation of busway lanes and so forth. But congestion still often occur until ini.Oleh therefore required the active role of road users themselves to be able to overcome the jam. One of the most effective ways is to find an alternative route that can be passed. Therefore we tried to address using Fuzzy Logic Mamadani and Dijkstra's algorithm to find the fastest and shortest path to include the factor of speed and travel time as well as leisure broad scope. Keywords: Dijkstra Algorithm, Fuzzy logic Mamdani, quickest route